Vedibandha (basal mouldings) of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The vedibandha (basal mouldings) of the Mahanaleshwar Temple are also divided as per this plan. In elevation, the mouldings consist of a jadyakumbha, gajathara, narathara, and a plain band followed by a broad kumbha moulding, kalasha, and kapotali. All these form the vedibandha section of the temple. The jadyakumbha (lotus-shaped moulding) has decorative motifs called the padma (lotus) and ardharatna (half diamond motifs). Just below the central kumbha (pot), the mouldings are punctured with a pranala, a water chute that facilitates the passage of water from the inside of the garbhagriha (sanctum sanctorum).